The Microbiology and Biochemistry of Anaerobic Bioreactors with Relevance to Domestic Sewage Treatment - O’Flaherty, Vincent; Collins, Gavin; Mahony, Thérèse (Reviews in environmental science and biotechnology, 2006)
Anaerobic granular and fixed-film reactors have been successfully operated for wastewater treatment at full scale for over two decades and represent a sustainable, energy-producing approach, which is increasingly being directed towards treatment of domestic sewage. Research over the past two decades, and significant operational experience, has demonstrated that there are no fundamental microbiological barriers to the implementation of AD for domestic sewage treatment in regions with warm and temperate climates. Despite this, the underlying microbiology of methanogenesis is not fully understood and novel groups of microbes have been identified in sludge, with unknown functions. The methanogenic process has recently been subject to systematic investigation using newly developed analytical and microbiological approaches. A combination of process monitoring, physiological, molecular microbiological and microscopic methods are beginning to generate a comprehensive, integrated data set at micro-organism, granule and reactor level and the current state of knowledge is reviewed here. Information on the formation of granules, on the relationship between reactor operating conditions and microbial consortia and on the impact of process changes on the microorganisms in reactors will, in future, enable the link between the processes occurring at microorganism level (scale ca.1km-1mm) and the processes occurring within reactors (scale >1m), which will enhance the efficiency and applicability of anaerobic sewage treatment.